ANALISIS FAKTOR YANG MEMPENGARUHI PENDAPATAN WARUNG ECERAN DALAM MENGHADAPI MINIMARKET BERJEJARING DI KECAMATAN KUTA UTARA KABUPATEN BADUNG - Darma Yanti, Kadek Bunga; Purbadharmaja, Ida Bagus Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
This study aims to analyze the effect of length of business, working hours, business distance, and culture of humanism simultaneously and partially on the income of traditional retail stalls in dealing with minimarkets in North Kuta District, Badung Regency. The study used a sampling method with quota sampling, where the number of samples was 96 stalls. The analysis technique used is Binary Logistic Regression Model analysis. The results showed that the length of business, working hours, distance of business, and the culture of humanism simultaneously had a significant effect on the income of traditional retail stalls in dealing with minimarkets in North Kuta District, Badung Regency. The length of business and the culture of humanism partially have a positive and significant effect on the income of traditional retail stalls in dealing with minimarkets in North Kuta District, Badung Regency. Working hours partially have a negative and significant effect on the income of traditional retail stalls in dealing with minimarkets in North Kuta District, Badung Regency. While length of business partially has a negative and significant effect on the income of traditional retail stalls in dealing with minimarkets in North Kuta District, Badung Regency.